Indonesian red chilli (Capsicum annuum L.) capsaicin and its correlation with their responses to pathogenic Fusarium oxysporum - Rejeki Siti Ferniah; Sri Pujiyanto; Hermin Pancasakti Kusumaningrum (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2018)
Red chili is a commercial crop for the food industry in Indonesia. There are some categories of red chili based on their pungency. The hot chili usually has more capsaicin than the sweet chili. Some cultivars may have more resistance to pathogen infection than the others. This research aimed to analyze the disease resistance of red chili cultivars from Indonesia against pathogenic Fusariumoxysporum and the correlation with capsaicin contents. Disease resistance was examined by determination of the Disease Severity Index (DSI) 15 dpi (days post inoculation). The correlation was analyzed by the regression coefficient. The result showed that the most resistance cultivar against F. oxysporum was Branang, while Lembang-1displayed the contrary. There was not a correlation of capsaicin content with the chili resistance to F. oxysporum.